Upward Continuation of Subsurface Anomalies Utilizing Magnetic Data in The Bedadung Watershed, Jember City - Yudhistira Adi Nugraha; Puguh Hiskiawan; Supriyadi Supriyadi (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2015)
Magnetic method is a geophysics method to determine the kind of subsurface material in certain depth by identifying the magnetic characteristics of rock based on the value of magnetic suspetibility. The data analysis described the subsurface anomaly using upward continuation filter. It separated local anomaly and regional anomaly by lifting research area in certain elevation. The raw data research was the total of magnetics data around Bedadung watershed, Jember. It was proceeded to obtaine magnetic anomaly curve on 5 line in contour map. It was digitalized and use as data input of magpick and upward continuation filter program. Upward continuation program was conducted using variation of area elevation in each track from 1 m up to 30 m. magnetic anomaly from this program is compared to magpick result showed that the magnetic anomaly curve on each line have good suitability with the accuracy 0,93%. Therefore, the continuation program become the alternative in magnetic data processing.